Serum bile acids in liver disease. Issue 2 (February 1971) - Neale, G.; Lewis, B.; Weaver, V.; Panveliwalla, D.
Abstract : Serum bile acids have been measured in patients with a wide variety of liver diseases using a technique which separates the major individual conjugated and free bile acids. Total serum bile acids may be elevated up to 100 times the normal concentration in patients with liver disease and this increase consists largely of conjugated bile acids. The ratio of glycine-conjugated to taurine-conjugated bile salts is low in all types of liver disease and this is found particularly in the serum of patients with obstructive jaundice. There is a decrease in the ratio of trihydroxy:dihydroxy cholanic acid in patients with cirrhosis.